BIOMECHANICAL AND BIOLOGICAL PROPERTIES OF BIOMATERIALS USED IN COMPLEX ORAL REHABILITATION - Berescu Maria-Miruna; Soponariu Ionela-Vergina; Agop-Forna Doriana; Hutanu Vasile Constantin; Hutanu Petruta Iuliana; Norina Forna (Romanian Journal of Medical and Dental Education)
Understanding the properties of dental biomaterials is important for comparison with the properties of hard and soft oral tissues before clinical applications. Various dental restorations tend to fail due to a number of reasons, such as misalignment or mechanical failure. Dental restorations are sometimes incompatible with the supporting oral tissues due to interface or substrate failure. Although no dental biomaterials have been reported to have properties to date, it is worth specifying that the performance and clinical success of dental biomaterials are strongly associated with their physical, mechanical, and biological properties. Ideally, the properties of biomaterials should closely match the properties of the lost tissues to be replaced.